MiR-134 modulates chronic stress-induced structural plasticity and depression-like behaviors via downregulation of Limk1/cofilin signaling in rats. (15th March 2018) - Fan, Cuiqin; Zhu, Xiuzhi; Song, Qiqi; Wang, Peng; Liu, Zhuxi; Yu, Shu Yan
Abstract: Increasing evidence has suggested that depression is a neuropsychiatric condition associated with neuroplasticity within specific brain regions. However, the mechanisms by which neuroplasticity exerts its effects in depression remain largely uncharacterized. In the present study we show that chronic stress effectively induces depression-like behaviors in rats, an effect which was associated with structural changes in dendritic spines and synapse abnormalities within neurons of the ventromedial prefrontal cortex (vmPFC). Moreover, unpredictable chronic mild stress (UCMS) exposure significantly increased the expression of miR-134 within the vmPFC, an effect which was paralleled with a decrease in the levels of expression and phosphorylation of the synapse-associated proteins, LIM-domain kinase 1 (Limk1) and cofilin. An intracerebral infusion of the adenovirus associated virus (AAV)-miR-134-sponge into the vmPFC of stressed rats, which blocks mir-134 function, significantly ameliorated neuronal structural abnormalities, biochemical changes and depression-like behaviors. Chronic administration of ginsenoside Rg1 (40 mg/kg, 5 weeks), a potential neuroprotective agent extracted from ginseng, significantly ameliorated the behavioral and biochemical changes induced by UCMS exposure. These results suggest that miR-134-mediated dysregulation of structural plasticity may be related to the display of depression-like behaviors in stressed rats. The neuroprotective effects of ginsenoside Rg1, which produces an antidepressant like effect in this model of depression, appears to result from modulation of the miR-134 signaling pathway within the vmPFC. Graphical abstract: Highlights: UCMS induced depression-like behavior accompanied with neuronal structural changes in mPFC. UCMS induced miR-134 overexpression and Limk1/cofilin downregulation in mPFC. MiR-134 modulates the structural neuroplasticity via Limk1/cofiling signaling pathway in mPFC. Ginsenoside Rg1 ameliorated behavioral and neuronal structural changes induced by UCMS. Ginsenoside Rg1 ameliorated the dysregulation of miR-134-Limk1/cofilin signaling induced by UCMS.